TARIFFS AND REGIMES OF POWER CONSUMPTION - S. V. Batsova; S. V. Solonin (Литьë и металлургия)
Analysis of regimes of electro-consumption at RUP «BMZ» is carried out. It is shown that in conditions of rapid growth of prices for electric power one of the conditions of reduction of production expenses is to be the increase of efficiency of the electro-consumption regimes control.